420 Keep calm and intubate: incorporation of local safety checklists into practice at a tertiary neonatal unit. (17th August 2022) - Gregory, Ian; Fullerton, Lucy; Rauchaudhuri, Reshmi; Warrick, Catherine
Abstract : Aims: National Safety Standards for Invasive Procedures (NatSSIPs) have been created to optimise patient safety in response to learning from serious incidents and near misses. The purpose is to improve pre- and post-procedural safety as well as documentation. This quality improvement project aimed to develop and embed Local Safety Standards for Invasive Procedures (LocSSIPs) and procedure pro formas (formal documentation) for four commonly performed neonatal invasive procedures: intubation, central venous access, lumbar puncture and chest drain insertion. Methods: Three audit cycles have been performed: Cycle 1) Introduction of a paper LocSSIP checklist and procedure pro forma in May 2020 (data collection August 2020). Cycle 2) Training sessions on the use of the LocSSIP checklist and procedure pro formas for medical and nursing professionals at medical induction and in the neonatal multi-disciplinary academic programme from August to October 2020 (data collection November 2020). Cycle 3) Procedure pro formas converted into pre-configured templates in electronic patient records and paper LocSSIP procedural checklist made available as both a single laminated readily available prompt form and a paper document (data collection July 2021). After the third cycle a short feedback survey was undertaken to assess attitudes to the LocSSIPs and procedure pro formas amongst medical staff. Results: Use of the procedure pro forma has improved with each audit cycle: 40% in cycle 1 [n=30], 56% in cycle 2 [n=36], 72% in cycle 3 [n=50]. Invasive procedures performed on the NICU were more likely to be documented on a pro forma than those performed in other clinical areas such as labour ward/A&E (72% [n=50] vs 0% [n=11]). Successful invasive procedures were more likely than unsuccessful procedures to be documented (72% [n=54] vs 25% [n=12]). The documented use of the LocSSIP procedural checklist has remained largely static: 40% cycle 1 vs 44% cycle 2 vs 42% cycle 3. The rate of LocSSIP use is similar for each procedure surveyed (Intubation 38% [n=8], Central line insertion 35% [n=31], Lumbar puncture 55% [n=11]). The survey of staff attitudes to the project showed that all staff who responded (6/6) preferred the electronic documentation, reporting it was easier to complete in the electronic format. They were less positive about the generic LocSSIPs form with only 2/6 liking it. Some staff preferred the separate paper forms for each procedure which contained lists of equipment and specific pre-procedural checks relevant to each procedure (e.g checking suction, oxygen supply, head position etc for intubation). Conclusion: This project has embedded the importance of clear documentation of invasive procedures among medical staff, with a standardised pro forma allowing medical trainees to easily document the salient information and post procedural checks. Additional education is needed to encourage documentation of unsuccessful procedures and procedures undertaken away from NICU. Laminated procedural checklists (including equipment) have been made readily available following the move towards electronic documentation. Further work is needed to increase use of the LocSSIP procedural time-out, and encourage a cultural change amongst medical and nursing staff to help them understand its importance in the prevention of errors.